A DIFFUSIVE TRANSPORT APPROACH FOR FLOW ROUTING IN GIS-BASED FLOOD MODELING - Liu Y.B.; Gebremeskel S.; De Smedt F.; Hoffmann L.; Pfister L. (My University, 2003)
This paper proposes a GIS-based diffusive transport approach for the determination of rainfall runoff response and flood routing through a catchment. The watershed is represented as a grid cell mesh, and routing of runoff from each cell to the basin outlet is accomplished using the first passage time response function based on the mean and variance of the flow time distribution, which is derived from the advection-dispersion transport equation. The flow velocity is location dependent and calculated in each cell by the Manning equation based on the local slope, roughness coefficient and hydraulic radius. The hydraulic radius is determined according to the geophysical properties of the catchment and the flood frequency. The total direct runoff at the basin outlet is obtained by superimposing all contributions from every grid cell. The model is tested on the Attert catchment in Luxembourg with 30 months of observed hourly rainfall and discharge data, and the results are in excellent agreement with the measured hydrograph at the basin outlet. A sensitivity analysis shows that the parameter of flood frequency and the channel roughness coefficient have a large influence on the outflow hydrograph and the calculated watershed unit hydrograph, while the threshold of minimum slope and the threshold of drainage area in delineating channel networks have a marginal effect. Since the method accounts for spatially distributed hydrologic and geophysical characteristics of the catchment, it has great potential for studying the influence of changes in land use or soil cover on the hydrologic behavior of a river basin.
Keywords: DIFFUSIVE WAVE; UNIT HYDROGRAPH; FIRST PASSAGE TIME DISTRIBUTION; GEOGRAPHICAL INFORMATION SYSTEM; FLOOD MODELING